SynchWeb: a modern interface for ISPyB - Fisher, S. J. (International Union of Crystallography, 2015)

(untitled) (J Appl Crystallogr)
SynchWeb is a modern interface to the ISPyB database. It significantly simplifies sample registration and is targeted towards live data collection monitoring and remote access for macromolecular crystallography. It adds a variety of new features including project management, an integrated diffraction image viewer, and a map and model viewer, as well as displaying results from automated analysis pipelines. Virtually all aspects of an experiment can be monitored through the web browser and the success of each experiment can be evaluated.